Radiotherapy in the preoperative neoadjuvant treatment of locally advanced rectal cancer - Yu, Zhen; Hao, Yuying; Huang, Yuhua; Ling, Ling; Hu, Xigang; Qiao, Simiao (Frontiers in Oncology, 2023)
Radiotherapy and chemotherapy are effective treatments for patients with locally advanced rectal cancer (LARC) and can significantly improve the likelihood of R0 resection. Radiotherapy can be used as a local treatment to reduce the size of the tumor, improve the success rate of surgery and reduce the residual cancer cells after surgery. Early chemotherapy can also downgrade the tumor and eliminate micrometastases throughout the body, reducing the risk of recurrence and metastasis. The advent of neoadjuvant concurrent radiotherapy (nCRT) and total neoadjuvant treatment (TNT) has brought substantial clinical benefits to patients with LARC. Even so, given increasing demand for organ preservation and quality of life and the disease becoming increasingly younger in its incidence profile, there is a need to further explore new neoadjuvant treatment options to further improve tumor remission rates and provide other opportunities for patients to choose watch-and-wait (W&W) strategies that avoid surgery. Targeted drugs and immunologic agents (ICIs) have shown good efficacy in patients with advanced rectal cancer but have not been commonly used in neoadjuvant therapy for patients with LARC. In this paper, we review several aspects of neoadjuvant therapy, including radiation therapy and chemotherapy drugs, immune drugs and targeted drugs used in combination with neoadjuvant therapy, with the aim of providing direction and thoughtful perspectives for LARC clinical treatment and research trials.